2010
DOI: 10.1002/pdi.1480
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow up of patients on U‐500 insulin: a case series

Abstract: The aim of this paper is to describe the long‐term effect of U‐500 insulin use on biomedical outcomes in a cohort of patients with diabetes mellitus.We carried out a case record review of 81 patients from a multicultural population who had received U‐500 insulin. We recorded data before the introduction of U‐500 and at data collection (February 2007) including: demographic information, weight, insulin dose, HbA1c, lipid profile and blood pressure.The results showed that the mean duration of treatment was 30±22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…We have recently reported long term follow up of patients on U-500 Human Actrapid 17. This retrospective audit reviewed 81 patients with T2DM on U-500 Human Actrapid over a mean duration of 30 months.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…We have recently reported long term follow up of patients on U-500 Human Actrapid 17. This retrospective audit reviewed 81 patients with T2DM on U-500 Human Actrapid over a mean duration of 30 months.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…In this study, increased self‐reporting of hypoglycaemia was documented on clinical charts, but the quality of life questionnaire suggested a trend towards reduced hypoglycaemia . Some series reported no episodes of severe hypoglycaemia . Davidson et al reported one severe episode of hypoglycaemia occurring after a missed meal .…”
Section: Clinical Effectivenessmentioning
confidence: 62%
“…Table summarizes the published case series which focus mainly on the use of U‐500 insulin MDI regimens . All the studies showed a clinically significant mean reduction in HbA1c of >11 mmol/mol (1%).…”
Section: Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…1 U-500R subcutaneous injections can significantly reduce hemoglobin A1c (HbA1c). 2 Its use via continuous subcutaneous insulin infusion (CSII) has been reported up to 12 months. This was associated with HbA1c reduction between 1.2% and 3.5%, weight gain, no change in total daily dose (TDD) of insulin, infrequent hypoglycemia, increased patient satisfaction, and cost savings.…”
mentioning
confidence: 99%